Composición florística, estructura y diversidad vegetal en sistemas agroforestales tradicionales y silvopastoriles del cantón valencia, Provincia los ríos, año 2018. - Barragán Márquez, Mishelle Stefaníe (2019)
The present research to evaluate the floristic composition, structure and vegetal diversity in traditional and silvopastoral agroforestry systems of the Valencia canton. Thirty sampling units (UM) were established, for the analysis of floristic composition, the ecological parameters were used: Frequency, Abundance and Absolute Dominance, while for plant biodiversity the Shannon, Simpson and Jaccard indices were used. In addition to the cluster analysis. A total of 43 families, 92 genera, and 122 species with a total of 1396 individuals were recorded in the agroforestry systems, being the Leguminosae and Arecaceae family the most representative. The species Citrus sinensis and Persea americana recorded the highest presence in the sampling units. According to the analysis of absolute frequencies, the Theobroma cacao, Citrus sinensis and Cordia alliodora species presented a greater number of individuals. The Shannon index determined an average diversity in sampling units 15, 9, 13 in silvopastoral systems, and units 15 and 5 in traditional agroforestry systems. The percentage of similarity between the sampling units does not exceed 50% of similar species in the agroforestry systems under study, the UM3 and UM5 registered greater similarity in the silvopastoral system and the units UMC9 and UMC7 in the traditional agroforestry system. According to the T-student average separation test at 95% probability, traditional agroforestry and silvopastoral systems present significant differences. Key words: Agroforestry systems, biodiversity, floristic composition, vegetal structure, similarity.